(untitled) (Journal of Hama University, 2021)
The aims of this paper have been to develop a measure that summarizes the banking sector’s condition in a country such as Syria; and to provide a framework that could help policymakers to predict the development of the banking sector’s condition. The anxiety index was created on the basis of 11 variables, which combined several types of variables (the market price variable for the bank’s shares and variables calculated from the balance sheet data and the variables measuring banking risks) .Our anxiety index estimates the banking sector’s condition on a continuous scale ranging from tranquil periods to severe crisis. It distinguishes itself from the traditional binary indicators found in the literature because it describes a continuous range of states rather than just differentiating crises from tranquil periods. This characteristic makes it particularly appropriate for depicting banking sectors, which rarely (or never) experience severe crises. It is the first time that anxiety index focusing on the banking sector in Syria has been constructed